Numerical limit analysis of steel-reinforced concrete walls and slabs. (November 2015) - Pisano, A.A.; Fuschi, P.; De Domenico, D.
Highlights: Peak load prediction of steel-reinforced concrete walls and slabs. Finite element procedures for nonstandard limit analysis. Menétrey–Willam type yield condition for concrete. Formulation in the principal stress space through Haigh–Westergaard coordinates. Validation by numerical simulation of experimental tests on large-scale prototypes. Abstract: A limit analysis based design methodology is hereafter proposed and applied for the peak load evaluation of steel-reinforced concrete large-scale prototypes of structural walls and slabs . The methodology makes use of nonstandard limit analysis and predicts the peak load multiplier of the analyzed structures by detecting an upper and a lower bound to it. Some useful hints on the collapse mechanism the structure will exhibit at its limit state is also attainable. To check the reliability of the numerically detected peak loads and failure modes a comparison with experimental laboratory findings, available for the large-scale specimens considered, is presented.